β-caryophyllene reduces inflammation to protect against ischemic stroke by suppressing HMGB1 signaling - Yuchun Wang; Yang Yang; Tuo Meng; Shengwei Liu; Jingdong Liu; Daohang Liu; Bharati Laxman; Sha Chen; Zhi Dong (Molecular Medicine)
Abstract Background Ischemic stroke is characterized by high mortality and high disability rates and accounts for the vast majority of current stroke cases. Reperfusion after surgical treatment can cause serious secondary damage to ischemic stroke patients, but there are still no specific drugs for the clinical treatment of ischemic stroke. Inflammation plays a critical role in ischemia and reperfusion injury, highlighting the urgent need for new anti-inflammatory targets and therapeutic agents. High-mobility group box-1 (HMGB1) is highly expressed in both neuronal cell bodies and axons and has been found to have late proinflammatory effects; thus, the role of HMGB1 in stroke has recently become a hot research topic in critical care medicine. An increase in HMGB1 expression leads to the aggravation of inflammatory reactions after ischemic stroke. B-caryophyllene (BCP) is a natural drug with anti-inflammatory effects. However, whether HMGB1 is involved in the anti-inflammatory mechanism of BCP is still unknown. We aimed to investigate the relationship between HMGB1 and BCP in in vivo and in vitro ischemic stroke models. Methods A middle cerebral artery embolism model was established in mice by thread thrombus, and primary neurons were subjected to oxygen‒glucose deprivation and reoxygenation (OGD/R) in vitro. In vitro, the HMGB1 DNA overexpression virus(GV-HMGB1)or the HMGB1 DNA silencing virus(RNAi-HMGB1)was injected into the lateral ventricles of mice.. Results HMGB1 expression increases after ischemic stroke and further affects the expression of TLR4, RAGE and other related inflammatory factors, thus reducing the inflammatory response and ultimately protecting against injury. These results confirmed the effect of HMGB1 on TLR4/RAGE signaling and the subsequent regulation of inflammation, oxidative stress and apoptosis. Furthermore, BCP potentially alleviates ischemic brain damage by suppressing HMGB1/TLR4/RAGE signaling, reducing the expression of IL-1β/IL-6/TNF-α, and inhibiting neuronal death and the inflammatory response. Conclusion These data indicate that BCP exerts a protective effect against ischemic stroke-induced inflammatory injury by regulating the HMGB1/TLR4/RAGE signaling pathway, which provides new insights into the mechanisms of this therapeutic candidate for the treatment of ischemic stroke.